Spectral theory and asymptotics of differential equations : proceedings of the Scheveningen Conference on Differential Equations, the Netherlands, September 3-7, 1973 - Jager, E. M. de (Eduardus Marie de) (North-Holland mathematics studies, 1974)
Proceedings of the Scheveningen Conference on Differential Equations, the Netherlands.